1987
DOI: 10.1097/00005650-198701000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness Analysis of End-stage Renal Disease Treatments

Abstract: The cost-effectiveness of various end-stage renal disease (ESRD) treatments was compared using two different cost measures. The first measure, gross social costs, excluded output gains due to treatment, whereas the second measure, net social costs, included output gains from both market and nonmarket activities. The cost-effectiveness criterion was the cost-per-life year gained or the implicit value of a year of life. The lower the cost-per-life year gained, the more costeffective the treatment was. Four ERSD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
3

Year Published

1991
1991
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 12 publications
0
31
0
3
Order By: Relevance
“…[46][47][48][49][50][51][52][53][54][55][56][57] The studies with strong designs included four comparative observational studies 16,42,44,45 and two systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[46][47][48][49][50][51][52][53][54][55][56][57] The studies with strong designs included four comparative observational studies 16,42,44,45 and two systematic reviews.…”
Section: Resultsmentioning
confidence: 99%
“…[46][47][48][49][50][51][52][53][54][55][56][57] The studies with strong designs included four comparative observational studies 16,42,44,45 and two systematic reviews. 12,43 Many of the studies reported costs and outcomes separately and/or reported costs per life-year saved, but appropriately did not calculate incremental cost-effectiveness or cost-utility ratios, because virtually all the evidence indicates that home haemodialysis costs less than hospital haemodialysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Kidney transplantation, for example provides a much higher quality of life than the alternative, outpatient dialysis. (49,50) But this increased quality of life comes at a high monetary cost. In this case, society has decided that the cost of kidney transplantation is "worth" the quality of life improvement and as such, this procedure is frequently performed.…”
Section: Discussionmentioning
confidence: 99%